Faktor-Faktor yang Mempengaruhi Kinerja Finansial Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Immanuela, Intan; Purbandari, Theresia; Ananda, Tiara Riszky (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2015)
The healthy and efficient financial performance is the important thing to reach thr greatest profit in the goverment. The goverment have to make an analysis of financial report in order to control the financial performance in a goverment and to compare the goverment’s condition in several years. There are many factors that influence the financial performance. This research is aimed to examine the influence of institutional ownership, an invesment decision, age, and the financial leverage against the financial performance. The population in this research is manufacturing company who enrolled in BEI in 2011-2013. The sample used in this research is 75 companies taken by applying the technique of purposive sampling. Engineering analysis used to test the hypothesis. The technique analysis use double regression linear (multiple regression). The result of this research shows that the institutional ownership and age of the company significant on the financial performance while the decision of the investment and also financial leverage do not significant on the financial performance